Practice of paediatric orthopaedics - Diab, Mohammad (Lippincott Williams & Wilkins/Wolters Kluwer, 2016)
"Profusely illustrated basic book on pediatric orthopaedics aimed at the resident in orthopaedics, the general orthopaedic surgeon, and the pediatrician. It is densley packed with relevent clinical information and a multitude of illustrations presented in a highly structured style"--Publisher's description.